Internet connectivity disruption in Pakistan (Pakistan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Pakistan. Data sourced from IODA.
Network Disruption Incident ID: PK-2026-0137. Severity: critical. Confidence: 67%